Brotación de encinas (Quercus ilex subsp. ballota) con edades elevadas. Experiencias en el monte de Riofrío (Segovia) - SERRADA, R.; BRAVO, J. A.; ROIG, S. (Invest. Agrar.: Sist. Recur. For. Fuera de Serie, 2004)
Results from an experiment with the objective of studying the sprouting capability —shoots of stump or root— on aged holm-oak trees are shown in this paper. Site of study is located in Riofrío forest, at 960 m a.s.l. at north facing slope of Guadarrama range (Central mountain range), on deep siliceous soils. After an ecological and dasonomic inventory 24 aged trees were fellen; dbh of fellen trees vary from 22.3 to 73.2 cm and age was estimated to be between 70 and 251 years. Contingence tables and logistic regression were used to test the dependence relationship among trees characteristics and the intensity of subsequent sprouting. One period growth after felling, 13 trees (62%) among the live ones (21) that had been felled present some shoots; after three growth periods, the same portion raised to 81% (17). We found only shoots of stump in 65% of the trees that had sprouted; 12% of trees that have only shoots of root and 23% of the trees with both types of shoots. Neither shoot production nor shoot type —stump or root— seems to be influenced by age.
Keywords: coppice; old holm-oak; Regeneration; shoot of root; shoot of stump; sprouting capability; viability

DETERMINACIÓN DE ROTACIONES ÓPTIMAS EN LA APLICACIÓN DE RESALVEOS DE CONVERSIÓN A MONTE ALTO EN TALLARES DE ENCINA Y DE QUEJIGO EN LA ZONA CENTRAL DE LA PENÍNSULA IBÉRICA. - BRAVO, J. A.; SÁNCHEZ, I.; SERRADA, R. (III Congreso Forestal Español, 2001)
Conversion thinning seems to be a good option for most of the coppicce forests of holm oak and gall oak, where the lack of management is causing severe problems. Intensity and rotation of thinning are the two main parameters to be studied. This paper deals with the second one. Six coppicce forests of holm oak and two for gall oak in the Guadalajara province where selected. Those stands had been thinned in a known date, and have been compared with near control stands, which have not been thinned in the past. Diameter growth after thinning has been studied throught rings count and ring width measurement in both kind of stands. 129 trees of holm oak and 79 trees of gall oak have been studied. The main conclusions are the evidence of a significant growth of diameter in holm oaks that is present 11 years after the thinning, while in gall oak results are not so clear. In gall oak just one site showed a positive answer to thinning, that was present until 17 years after. K.W.:
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español issue: 1 pub-location: Granada
Keywords: conversion thinning; coppicce forest; gall oak; Growth; Holm oak; rotation